Entry Barriers, Idiosyncratic Distortions, and the Firm-Size Distribution - Fattal-Jaef, Roberto N. (World Bank, Washington, DC, 2019)
This paper studies the interaction between entry barriers and idiosyncratic distortions in the context of a standard model of firm dynamics. It derives a strategy to infer entry barriers based on the combination of cross-country data on average firm size, cross-country estimates of idiosyncratic distortions, and equilibrium conditions of the theory. It finds sizable entry barriers that correlate positively with income per-capita. The TFP gains from complete reversals of distortions range between 20 and 50 percent. Idiosyncratic distortions are most distortive in low income countries whereas entry barriers are relatively more detrimental in advanced economies. The study also finds that distortions tend to mitigate each other's negative effect on TFP.